The Influence of Narcissistic Behavior and Self-Esteem on Accountants' Self-Control in Interacting on Social Media with Accountant Professional Ethics as an Intervening Variable - Fauziah, Ratih; Khadzil, Syed Azlan Aljaffree Syed (Asosiasi Dosen Akuntansi Indonesia, 2023)
This research aims to determine the influence of narcissistic behavior and self-esteem on accounting professional ethics and to determine the influence of narcissistic behavior and self-esteem on accounting self-control in interacting on social media. The sample in this study was determined based on the Roscoe formula with 100 respondents. The analytical tool used is Smart Partial Least Square (SmartPLS) 4.0, with the Structural Equation Modeling (SEM) analysis method. The research results show (1) Narcissistic behavior influences Accountant Professional Ethics, (2) Self - Esteem influences the Professional Ethics of Accountants, (3) Narcissistic behavior has no effect on accountants self-control, (4) Self - Esteem and Accountant Professional Ethics influence the Accountant's Self-Control, (5) Narcissistic behavior does not affect accountants' self-control through accountants' professional ethics in interacting on social media, 6) Self - Esteem influences Accountants' Self Control through Accountants' Professional Ethics in interacting on social media.